Análisis jurídico de la legalización y regulación de los canones de arrendamiento a través de la normativa local en el cantón Guaranda. - Sinche Veintimilla Diana Mariuxi (2024)
The purpose of this research is to conduct an analysis of the legislative authority granted by law to Decentralized Autonomous Governments to control various aspects according to the local reality of each territory. Among these aspects is the power to legally regulate lease rates within their territorial jurisdiction. This responsibility has a broad scope and extends to influencing the management of family, individual, local, and state economies. The global overpopulation results in a lack of housing, a social reality palpable every day in Ecuador. The legal figure of leasing is an option embraced by many individuals. In our country, this figure is regulated and legally recognized through the Tenancy Law and the Civil Code, and is mentioned in a relevant section of the Organic Code of Territorial Organization, Decentralization, and Autonomy. The regulation stipulated in the Civil Law relates to the institution of the lease contract and the obligations arising from the signing of the legal instrument. The specific law establishes generalities in a general manner. However, it is the Organic Code of Territorial Organization, Decentralization, and Autonomy that determines and empowers Decentralized Autonomous Governments to regulate the maximum amounts of lease rates. These rates logically cannot be imposed informally under any circumstances; instead, they must be based on updated land registries, market studies, and the economic capacity of the population. Thus, with technical expertise and legal advice, local legislation can be enacted to establish lease rates that reflect the local reality and the genuine needs of the population specifically in the Guaranda. This research focuses on legally analyzing the form and methodology by which Decentralized Autonomous Governments can regulate lease rates objectively, in accordance with the law. It aims to establish regulations that prevent abuses by 5 property owners in imposing lease rates, while also ensuring that such regulations do not harm the interests of property owners. Instead, the goal is to establish regulations that, as explained throughout the research, respond to social needs within the local context. It is emphasized that the primary objective of the law is to regulate social and commercial relations within the state. The methodology of this research is of a basic nature, also known as fundamental or pure research, which focuses on the review of theoretical and conceptual knowledge without immediate practical application. It was utilized to gather relevant information concerning national and local legal frameworks related to leases and lease rates in Ecuador, as well as to review previous studies and academic literature on the topic, including laws, regulations, jurisprudence, and any other relevant documents. Both inductive and deductive methods were employed, along with field tools such as interviews and surveys, to analyze the quantitative data obtained from the questionnaires. Keywords: Lease rate, Ordinance, Tenancy Law, Decentralized Autonomous Government, Legislation.